Dynamics of a vapor nanobubble collapsing near a solid boundary. (November 2015) - Magaletti, Francesco; Gallo, Mirko; Marino, Luca; Casciola, Carlo Massimo
Abstract: In the present paper a diffuse interface approach [1] is used to address the collapse of a sub-micron vapor bubble near solid boundaries. This formulation enables an unprecedented description of interfacial flows that naturally takes into account topology modification and phase changes (both vapor/liquid and vapor/supercritical fluid transformations). Results from numerical simulations are exploited to discuss the complex sequence of events associated with the bubble collapse near a wall, encompassing shock-wave emissions in the liquid and reflections from the wall, their successive interaction with the expanding bubble, the ensuing asymmetry of the bubble and the eventual jetting phase.